Impact of recession to companies marketing activities - Virtanen, Ville (My University, 2011)
Recession is interesting and multidimensional phenomenon, which has been on the headlines lately. Phenomenon has been studied earlier and the consequences of it have been target of interest for business and academic. Purpose of this study is to explore that Will companies change or adjust their marketing activities due to recession to survive better from it? Marketing literature about marketing mix and the use of different marketing activities construct the base for this study. Recession has been studied widely in academic field, but only few studies have focused only on marketing mix elements and marketing activities during recession. Still, some earlier studies have clear evidence that companies which increase marketing activities during recession will face the increase of market share and sales. In this study there was constructed theoretical model, which is based on marketing mix elements and previous studies. This theoretical model suggested specific marketing activities, which could improve the performance of companies during recession. According to findings of empirical study, recession was not considered as major threat in the case companies of this study. All the case companies announced that they do not change their marketing strategy due to recession. Other major influencing factors for these companies were general strategy, marketing strategy, industry, nature of products and customers. Companies in this study did not consider recession as opportunity to increase marketing activities in this study despite the results of previous studies. Empirical study proved that recession had only minor influence of case companies. Still, there was some evidence in this study that increased marketing activities can have positive influence on companies’ performance during recession. One of the case companies faced increased turnover and sales during years 2007-2010, when they increased marketing activities.
Keywords: recession; downturn; marketing mix; marketing activities; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|